Cost-benefit considerations of lockdowns: What are we missing? - Thomas Obst; Dan Schläger (Institut der deutschen Wirtschaft (IW), 2021)
A cross-country comparison shows similar behavioural adaptations of individuals despite different degrees of stringency of the respective lockdown in place. In Germany, during the first lockdown in spring 2020 mobility fell by 45 percent, while in Sweden it also decreased by 27 percent during the same period. A comprehensive cost-benefit analysis is crucial to better evaluate the efficacy of lockdowns and implied trade-offs. – – Ein länderübergreifender Vergleich zeigt ähnliche Verhaltensanpassungen von Individuen trotz unterschiedlicher Lockdown-Maßnahmen. In Deutschland ging die Mobilität während des ersten Lockdowns 2020 um 45 Prozent zurück, in Schweden sank sie im gleichen Zeitraum um 27 Prozent. Eine umfassendere Kosten-Nutzen-Analyse ist entscheidend, um die Wirksamkeit und verursachte Kosten von Lockdowns besser bewerten zu können.
Keywords: 330